Expression of programmed death‐1 in skin biopsies of benign inflammatory vs. lymphomatous erythroderma. (21st August 2014) - Çetinözman, F.; Jansen, P.M.; Willemze, R.
Abstract : What's already known about this topic? Histological differentiation between Sézary syndrome (SS) and erythrodermic inflammatory dermatoses (EID) is often difficult. Programmed death‐1 (PD‐1) is strongly expressed by the neoplastic cells in skin biopsies of SS suggesting diagnostic potential, but similar studies in EID are lacking. What does this study add? PD‐1 is expressed not only by CD4 + neoplastic T cells in SS, but also by activated (epi)dermal CD8 + T cells in EID. Expression of PD‐1 by > 50% of CD4 + T cells and expression of CD7 by ≤ 20% of the infiltrating T cells strongly support a diagnosis of SS. Summary: Background: Histological differentiation between Sézary syndrome (SS) and erythrodermic inflammatory dermatoses (EID) can be very difficult. Recent studies show that programmed death‐1 (PD‐1) is strongly expressed by the neoplastic cells in skin biopsies of SS, while similar studies in EID are lacking. Objectives: To determine whether the number and distribution of PD‐1 + T cells could be used as an adjunct in the differentiation between SS and EID. Methods: Expression of PD‐1 and a panel of T‐cell markers was investigated in skin biopsies from 30 patients with various types of EID (12 idiopathic, 10 atopic, six psoriatic and two paraneoplastic) and 25 patients with SS. Results: Expression of PD‐1 by > 50% of the infiltrating T cells was observed in 23 of 25 (92%) SS cases and in only four of 30 (13%) EID cases. PD‐1 is expressed by neoplastic CD4 + T cells in SS, while in contrast, PD‐1 was predominantly expressed by dermal and epidermal CD8 + T cells in EID. Expression of CD7 by ≤ 20% of the infiltrating T cells was observed only in SS (13 of 24; 54%), and not in any of the 30 cases of EID. Conclusions: While PD‐1 is expressed by CD4 + neoplastic T cells in SS, our results suggest that PD‐1 is expressed mainly by activated dermal and epidermal CD8 + T cells in EID. Expression of PD‐1 by > 50% of CD4 + T cells and expression of CD7 by ≤ 20% of the infiltrating T cells strongly support a diagnosis of SS in skin biopsies of patients with erythroderma.